Rationale and design of the HIP fracture Accelerated surgical TreaTment And Care tracK (HIP ATTACK) Trial: a protocol for an international randomised controlled trial evaluating early surgery for hip fracture patients. Issue 4 (1st May 2019) - Borges, Flavia K; Bhandari, Mohit; Patel, Ameen; Avram, Victoria; Guerra-Farfán, Ernesto; Sigamani, Alben; Umer, Masood; Tiboni, Maria; Adili, Anthony; Neary, John; Tandon, Vikas; Sancheti, Parag K; et al.
Abstract : Introduction: Annually, millions of adults suffer hip fractures. The mortality rate post a hip fracture is 7%–10% at 30 days and 10%–20% at 90 days. Observational data suggest that early surgery can improve these outcomes in hip fracture patients. We designed a clinical trial—HIP fracture Accelerated surgical TreaTment And Care tracK (HIP ATTACK) to determine the effect of accelerated surgery compared with standard care on the 90-day risk of all-cause mortality and major perioperative complications. Methods and analysis: HIP ATTACK is a multicentre, international, parallel group randomised controlled trial (RCT) that will include patients ≥45 years of age and diagnosed with a hip fracture from a low-energy mechanism requiring surgery. Patients are randomised to accelerated medical assessment and surgical repair (goal within 6 h) or standard care. The co-primary outcomes are (1) all-cause mortality and (2) a composite of major perioperative complications (ie, mortality and non-fatal myocardial infarction, pulmonary embolism, pneumonia, sepsis, stroke, and life-threatening and major bleeding) at 90 days after randomisation. All patients will be followed up for a period of 1 year. We will enrol 3000 patients. Ethics and dissemination: All centres had ethics approval before randomising patients. Written informed consent is required for all patients before randomisation. HIP ATTACK is the first large international trial designed to examine whether accelerated surgery can improve outcomes in patients with a hip fracture. The dissemination plan includes publishing the results in a policy-influencing journal, conference presentations, engagement of influential medical organisations, and providing public awareness through multimedia resources. Trial registration number: NCT02027896 ; Pre-results.